Creating Social Cohesion in an Interdependent World Experiences of Australia and Japan - Healy, Ernest; Arunachalam, Dharma; Mizukami, Tetsuo; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Creating Social Cohesion in an Interdependent World brings together Australian and Japanese scholars to examine the ways in which their two very different societies have dealt with challenges to their cultural and institutional fabric, and social cohesion associated arising from the acceleration of global interdependence during recent decades.
Keywords: Social sciences; Sociology; Social Sciences; Sociology, general; Electronic books